The Business Behind the Blessings: A Critical Review of Financial Practices At Masjid Agung At-Taqwa - Idham Mahrivi; Waizul Qarni; Atika Atika (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to determine the financial management programs implemented at the At-Taqwa Mosque in Southeast Aceh Regency in empowering the community through financial management. The type of research used in this study is qualitative with descriptive qualitative analysis. Types of data collection were carried out using interviewtechniques, observation, documentation, and literature with the research subject of money management at the AT-Taqwa Mosque. The results of the study indicate that the At-Taqwa Mosque not only manages money but also participates in mosque-based community empowerment through the money given. Empowerment is also realized through empowerment programs in the economic field such as productive money, healthy carts and providing training to mustahiq. Good economic empowerment indicates that mustahiq also have good economic quality. This is due to the changing mindset of the community that is increasingly developing about efforts to improve the standard of living to be better than before. Therefore, economic empowerment can improve the welfare, income, and independence of mustahiq. The implication of this research is that Mosque Financial Management is not merely administrative, but has a social impact. Through effective fund management, At-Taqwa Mosque is able to carry out economic empowerment programs that directly address the needs of mustahiq (beneficiaries), thus providing a real impact on the lives of the community.Keywords: Money, Community Empowerment, Mustahiq, Mosque.